P222 Purely fibrostenotic Crohn's disease without chronic inflammation is uncommon – a histopathologic study of resected intestine. (25th January 2019) - Shivaji, U N; Evans, M; Critchlow, T; Smith, S C L; Iacucci, M; Ghosh, S; Cooney, R; Skordilis, K
Abstract: Background: Crohn's disease (CD) is a chronic inflammatory condition with multiple phenotypes of which the fibrostenotic type (B2) carries significant morbidity and risk of surgery. We have shown previously that stenotic segments are characterised by expansion of multiple layers of the intestine which can be quantitated by a novel scoring system. We characterised histological changes in resected ileal specimens using this scoring system. Methods: We identified all patients undergoing surgery for symptomatic stricturing CD unresponsive to anti-inflammatory therapy using the histopathology database at Queen Elizabeth Hospital in Birmingham, UK, between 2012 and 2017. Phenotypic data were recorded; most representative haematoxylin and eosin-stained section of specimens reviewed and evaluated for histological features of active and chronic inflammation, fibrosis, smooth muscle hyperplasia, neuronal hypertrophy, and adipocyte proliferation for each layer of bowel wall. Two independent pathologists applied the semi-quantitative scoring system. The percentage [%] of the possible maximum total score [PMTS] calculated: adjusted score [%] = [actual total score/PMTS] × 100. The correlations between different contributions to intestinal layers were calculated using Pearson's correlation coefficient. Results: Among 48 patients (M = 25; median age 45 years, range 21–72 years), median duration of disease was 7 years (range 3 months–39 years); 32 (66%) patients ileo-colonic disease (L3); 16 patients were on thiopurines, 19 on steroids and 4 on biologics. The histological grading in each layer of the intestine are shown in Table 1. In the mucosa, chronic inflammation was more prominent whereas fibrosis was predominant in the submucosa; chronic inflammation and muscular hyperplasia (MPH) were consistently prominent features across all layers of strictured bowel and had statistically significant correlation with fibrosis (Pearson correlation coefficient r = 0.339, p = 0.018 and r = 0.648, p < 0.001, respectively) Abstract P222 – Table 1. Histology scores. Conclusions: Our results suggest that pure fibrostenotic disease is uncommon and chronic inflammation is a prominent feature of this phenotype. In addition to fibrosis, muscle hyperplasia is an important component. Other components such as volume expansion, neuronal hypertrophy and adipose hyperplasia are likely to be important in specific layers of the bowel. This suggests that inflammation driven tissue remodelling leading to stricture formation is a complex process resulting in a multitude of changes and not simply characterised by excess deposition of fibrotic tissue.